MEWUJUDKAN ARGODADI SEBAGAI DESA INKLUSI BAGI DISABILITAS - Arni Surwanti; Eni Istianti2 Istianti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Development of Disadvantaged Regions and Transmigration has issued Guidelines for Facilitation ofInclusive Villages or disability-friendly villages, so that persons with disabilities can have the same opportunity to participate in development. The problem at this time argodadi village does not have data and perspectives on disability in its development, the community has not given attention and support to persons with disabilities, there are no village disability groups, people with disabilities are still low in welfare because it is difficult to access work, there are no policies at the village level related to the protection and fulfillment of disability rights. Through the inclusion movement from the village, it is hoped that the parties can play a role and encourage awareness for every member of the community about the importance of protection for persons with disabilities. The implementation method is to prepare Argodadi village to become an inclusion village by running 5 (four) stages of 9 (nine) stages to become an inclusion village. The result of this community service activity is the formation of 1 (one) community-based rehabilitation group in the village. There is a data base for people with disabilities at the village level, and 190 total data on persons with disabilities have been recorded. 1 (one) village disability group (KDD) wasformed, named Argodadi Pinilih. Training in the skills of persons with disabilities in mushroom cultivation and processed foods made from mushrooms. the composition of 1 (one) draft village regulation on the protection and empowerment of persons with disabilities. In order to achieve inclusion villages, the role ofthe government, the community, and persons with disabilities is needed. Abstrak Pembangunan Daerah Tertinggal dan Transmigrasi telah mengeluarkan Panduan Fasilitasi Desa Inklusif atau desa yang ramah pada disabilitas, sehingga penyandang disabilitas dapat memiliki kesempatan yang sama berpartisipasi dalam pembangunan. Permasalahan pada saat ini Desa Argodadi belum memiliki data dan perspektif disabilitas dalam pembangunannya, masyarakat belum memberikan perhatian dan dukungan pada penyandang disabilitas, belum ada kelompok disabilitas desa, penyandang disabilitas masih rendah kesejahteraannya karena sulit mengkases pekerjaan, belum ada kebijakan di tingkat desa terkait perlindungan dan pemenuhan hak disabilitas. Melalui gerakan inklusi dari desa diharapkan para pihak dapat berperan dan mendorong kesadaran bagi setiap anggota masyarakat akan pentingnya perlindungan pada penyandang disabilitas. Metode pelaksanaan adalah mempersiapkan desa Argodadi ini menjadi desa inklusi dengan menjalankan 5 (empat) tahapan dari 9 (Sembilan) tahapan untuk menjadi desa inklusi. Hasil kegiatan pengabdian masyarakat ini adalah terbentuknya 1 (satu) kelompok rehabilitasi berbasis masyarakat di desa. Adanya data base penyandang disabilitas tingkat desa, dan telah terdata 190 jumlah data penyandang disabilitas. Terbentuk 1 (satu) kelompok disabilitas desa (KDD), bernama Argodadi Pinilih. Pelatihan ketrampilan penyandang disabilitas dalam budidaya jamur dan makanan olahan dari berbahan dasar jamur. tersusunnya 1 (satu) draft peraturan desa tentang perlindungan dan pemberdayaan penyandang disabilitas. Guna menujudkan desa inklusi diperlukan peran pemerintah, masyarakat, dan penyandang disabilitas.